Thrombolysis after dabigatran reversal: A nation-wide Italian multicentre study, systematic review and meta-analysis. (March 2023) - Romoli, Michele; Matteo, Eleonora; Migliaccio, Ludovica; Gentile, Mauro; Mosconi, Maria Giulia; Scura, Giuseppe Maria; Naccarato, Marcello; Colangeli, Enrico; Candelaresi, Paolo; Andreone, Vincenzo; Giammello, Fabrizio; Fortunata Musolino, Rosa; et al.
Introduction: Recent anticoagulant intake represents a contraindication for thrombolysis in acute ischemic stroke. Idarucizumab reverses the anticoagulant effect of dabigatran, potentially allowing for thrombolysis. This nation-wide observational cohort study, systematic review, and meta-analysis evaluated the efficacy and safety of thrombolysis preceded by dabigatran-reversal in people with acute ischemic stroke. Patients and methods: We recruited people undergoing thrombolysis following dabigatran-reversal at 17 stroke centers in Italy (reversal-group), people on dabigatran treated with thrombolysis without reversal (no-reversal group), and age, sex, hypertension, stroke severity, and reperfusion treatment-matched controls in 1:7 ratio (control-group). We compared groups for symptomatic intracranial hemorrhage (sICH, main outcome), any brain hemorrhage, good functional outcome (mRS 0–2 at 3 months), and death. The systematic review followed a predefined protocol (CRD42017060274), and odds ratio (OR) meta-analysis was implemented to compare groups. Results: Thirty-nine patients in dabigatran-reversal group and 300 matched controls were included. Reversal was associated with a non-significant increase in sICH (10.3% vs 6%, aOR = 1.32, 95% CI = 0.39–4.52), death (17.9% vs 10%, aOR = 0.77, 95% CI = 0.12–4.93) and good functional outcome (64.1% vs 52.8%, aOR = 1.41, 95% CI = 0.63–3.19). No hemorrhagic events or deaths were registered in no-reversal group (n = 12). Pooling data from 3 studies after systematic review (n = 1879), reversal carried a non-significant trend for sICH (OR = 1.53, 95% CI = 0.67–3.50), death (OR = 1.53, 95% CI = 0.73–3.24) and good functional outcome (OR = 2.46, 95% CI = 0.85–7.16). Discussion and conclusion: People treated with reperfusion strategies after dabigatran reversal with idarucizumab seem to have a marginal increase in the risk of sICH but comparable functional recovery to matched patients with stroke. Further studies are needed to define treatment cost-effectiveness and potential thresholds in plasma dabigatran concentration for reversal.